'More laborious missions, and difficult, which is the universal Company'. Difficulties of the missionary work of the Company of Jesus in Philippines (1581-1768) - Descalzo Yuste, Eduardo (2016)
This article analyses the difficulties that the missionaries of the Society of Jesus had to confront in the Philippine Islands throughout Early Modern history. To do so, we reproduce first hand testimonies that offer a direct and unique perspective of how these men lived hard situations of shortage of men, isolation, extreme climate, mortal danger, etc.